Platelet Aggregation Induced by Plasma from Type IIB von Willebrand’s Disease Patients Is Associated with an Increase in Cytosolic Ca2+ Concentration - Francesconi, Maria Angela; Deana, Renzo; Girolami, Antonio; Pontara, Elena; Casonato, Alessandra (Thrombosis and Haemostasis, 1993)
The effect of type IIB von Willebrand’s factor (vWF) on platelet cytosolic Ca2+ ion concentration, measured by means of the probe fura 2, was investigated. Seven patients with type IIB von Willebrand disease (vWD) were studied. Addition of type IIB vWD plasma to platelet suspensions induced a cytosolic calcium increase accompanied by platelet aggregation. Both processes were completely abolished by addition of the calciumchelating agent EGTA, indomethacin, peptide RGDS, and monoclonal antibodies blocking the vWF binding site on GPIb-IX (LJIB1) or the cytoadhesive receptor on GPIIb-IIIa (LJCP8). The ADP-scavenger apyrase and the protein kinase C-inhibitor staurosporine partially inhibited the rate of the cytosolic calcium increase. No direct correlation between the extent of Ca2+ rise and the phenotypic expression of IIB vWD, such as the degree of spontaneous platelet aggregation or thrombocytopenia was apparent. It is suggested that aggregation and cytosolic Ca2+ increase in platelets exposed to plasma from type IIB vWD patients is mediated by a self-potentiating mechanism involving both GPIb and GPIIb-IIIa receptors as well as the thromboxane biosynthetic pathway.